Engraving of King Louis XIV of France visiting Paris in 1687 (Almanach... - Auteur inconnu (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Engraving of King Louis XIV of France visiting Paris in 1687 (Almanach royal).
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie